REVIEW EFEKTIFITAS MODEL COOPERATIVE LEARNING DALAM PEMBELAJARAN BAHASA - Samsu Armadi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
Cooperative learning has been implemented widely in teaching learning process resulting optimum outcomes in learning.  Five principles of learning in the cooperative learning are essential, making cooperative learning efficient and different from just placing students into groups.  This paper is a review of cooperative learning for language class.  However, the evidence indicates that cooperative learning is also applicable for lessons other than language class.